ADOLESCENT HEALTH PROBLEMS AND ADOLESCENT FRIENDLY HEALTH CLINIC FROM ADOLESCENTS' PERSPECTIVE (BESUT AND KUALA TERENGGANU): A QUALITATIVE RESEARCH - Nordiyanah Hassan; Khatijah A. Rahman; M. Aris Kasah; Mohd Jusoh (Malaysian Journal of Public Health Medicine, 2002)
A qualitative research was carried out in Besut and Kuala Terengganu to identify adolescents' health problems and needs from adolescent perspective, and to establish a priority area in the development of Adolescent Health Clinic in the district. A total of 61 adolescents were selected and divided into four groups and stratified according to age, 13-15 years old and 16 - 17 years old. Generally all participants wished to live in an environment free from negative health riskfactors. The obstacles they perceived were mainly related to lack of care or too much control by their parents. Some of them perceived that their parents in general had inadequate knowledge and skills on parenting. Among local behavioural problems mentioned were loafing, running away from home, vandalism, school absenteeism, aggressive behaviour, substance abuse, pre-marital sexual activities, "bohsia", "bohjan" and even involvement in crimes. More than half agreed that counselling service is important for adolescents, and it should be made available in the community preferably outside the schools. They perceived an adolescent friendly health clinic concept as an important concept that should be introduced. To them adolescent friendly health clinic is a clinic run by professionals who are knowledgeable, caring, good listeners, non-judgemental, and who exercise confidentiality. The clinic preferably should be situated in a location which is away from the present health facilities to avoid the image of a place for sick people. Clinic hours preferably during weekends, should provide appropriate technologies and situated in a comfortable ambience. Adolescent participation in the clinic was also mentioned as an important entity for adolescent friendly health services.